Modeling the different conformations of the human mitochondrial ADP/ATP carrier using AlphaFold and molecular dynamics simulations of the protein-ligand complexes - Virginia Quadrotta; Fabio Polticelli (Computational and Structural Biotechnology Journal)
The ADP/ATP Carrier (AAC), a member of the mitochondrial Solute Carrier Family 25 (SLC25), facilitates the exchange of cytosolic ADP for mitochondrial ATP across the inner mitochondrial membrane (IMM). It serves as a master regulator of the cellular ADP/ATP ratio and is involved in various pathologies, including cancer. Its transport mechanism involves a conformational transition that alternates the accessibility of the binding site between the cytoplasmic (c-state) and mitochondrial (m-state) sides of the IMM. In this study, the human AAC was used as a case study to evaluate the performance of AlphaFold2 (AF2) and AlphaFold3 (AF3) for structural modeling of members of the SLC25 family. The study also compared the AF3 approach for predicting protein-ligand complexes with the standard methodology of modeling followed by molecular docking. Both AF2 and AF3 display a bias toward the c-state conformation. On the other hand, ColabFold implementation of AF2 successfully generated the first ab initio structural model of the human AAC in the m-state conformation. Modeling of the complexes coupled to molecular dynamics (MD) simulations allowed to obtain structural insight into AAC’s substrate binding and stabilization mechanisms, and the possible effects of pathogenic mutations on its conformational dynamics and functionality. These analyses provided a deeper understanding of AAC’s alternating access mechanism and highlighted the potential of AF3 in modeling protein-ligand interactions, though only in the c-state. This work demonstrates the reliability of AlphaFold models when aligned with experimental data and provides further confirmation of their utility for investigating solute carriers and membrane proteins.